Fundamentals of Kalman filtering : a practical approach - 178922 Zarchan, Paul; Musoff, Howard; American Institute of Aeronautics and Astronautics (Reston, Va. : American Institute of Aeronautics and Astronautics)
Includes bibliographical references and index